Move Up, Live Up: Dance Activities as a Way of Motivating Students Participating in Progressive Limited Face-to-face Classes - Recede, Reynald Alfred A.; Bulay-og, Leah Sablayan; Reyes, Joyce E. (Future Science / FSH-PH Publications, 2023)
Dancing is a popular form of physical exercise. Researches have shown that dancing can increase self-esteem and improve our mind and body to become more productive. The aim of this study is to explore the impact of